2017
DOI: 10.1016/j.msksp.2016.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Y balance test has no correlation with the Stability Index of the Biodex Balance System

Abstract: The results of this study showed the YBT is not correlated with the SI-BBS as an assessment of postural stability. This finding has implications for researchers and clinicians using YBT results as the only measure of postural stability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 26 publications
(40 reference statements)
3
35
1
1
Order By: Relevance
“…More interestingly, the study revealed poor construct validity between measures, indicating that the selected methods of balance assessment examine unrelated constructs. This supports previous findings by Almeida et al that identified no significant correlation between the Y Balance Test and the Biodex SI. These findings support the growing body of evidence that the constructs of balance and postural stability are complicated and involve a series of unique motor systems that require a focused examination by a skilled clinician.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…More interestingly, the study revealed poor construct validity between measures, indicating that the selected methods of balance assessment examine unrelated constructs. This supports previous findings by Almeida et al that identified no significant correlation between the Y Balance Test and the Biodex SI. These findings support the growing body of evidence that the constructs of balance and postural stability are complicated and involve a series of unique motor systems that require a focused examination by a skilled clinician.…”
Section: Discussionsupporting
confidence: 93%
“…These two components of human performance serve as a foundation of stability prior to achieving more complex controlled mobility and skilled activities such as independent standing and walking . Postural control, or stability, represents an individual's capacity to maintain an upright position during both static and dynamic conditions, with or without the application of external perturbation or displacement of support surface . Posture is an angular measure from vertical describing the gravitational vector of the body's orientation .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These indices were calculated according to the degree of platform oscillation. Smaller values indicated higher stability rates for the individual [19]. Prior to testing, participants received the following instructions:…”
Section: Postural Stability Testmentioning
confidence: 99%
“…Les valeurs de corrélations sont modérées à bonne (r=0.57 à 0.78) [2]. Le YBT est peu corrélé avec la berg balance scale (BBS) chez les personnes âgées [11], et le test d'équilibre statique monopodal chez des sportifs loisirs [18].…”
Section: Validitéunclassified